Cuantificación de macronutrientes, calcio, fibra e identificación de vitaminas en mezcla fortificada de cereales y leguminosas distribuidas por el programa vaso de leche en el distrito de Shorey – Santiago de Chuco. abril – mayo 2014. - Aznarán Cruzado, Carmen Isabel (2014)
A mixture of fortified cereals and legumes distributed by the Program “Vaso de Leche” of the Shorey district – Santiago de Chuco, Departamento La Libertad was analyzed. The concentration of macronutrients, calcium, fiber and identify vitamins were determined. The Chemical Fehling, Kjeldahl, Soxhlet and Complexometric were the methods used. The results were: 62,66 % of carbohydrates; 20 % of fat; 7,28 % of protein; 5,1 % of ashes; 0,56 % of fiber; 605 mg of calcium and presence of vitamin A . The content of fat, proteins and carbohydrates were found within the ranges mentioned in the container of the product, while the content of calcium was found under the ranges; also into the liposolubles vitamins the product only contains vitamin A.